Association between Helicobacter pylori Infection and Diabetes: A Cross-Sectional Study in China - Sailimai Man; Yuan Ma; Cheng Jin; Jun Lv; Mingkun Tong; Bo Wang; Liming Li; Yi Ning (Journal of Diabetes Research)
Background. Studies suggest an association between H. pylori infection and extragastrointestinal disease. Limited studies provided conflicting results on the association between H. pylori infection and diabetes. The present study was aimed at examining the association between H. pylori infection and diabetes in a large health checkup population in China. Methods. A cross-sectional study was conducted; participants who attended health checkups at Beijing MJ Health Screening Center during 2017-2018 were included. H. pylori infection was diagnosed by 13C-urea breath test. Multivariate logistic regression analysis was performed to evaluate the association between H. pylori infection and diabetes. Results. The mean age of 13,397 participants was 43.8±12 years. The prevalence of H. pylori infection and diabetes was 28.2% and 8.1%, respectively. The prevalence of diabetes was higher among H. pylori-positive participants compared with their counterparts (8.9% vs 7.8%, p=0.05). After adjustment of age, sex, family history of diabetes, smoking, education, stroke, coronary heart disease, BMI, SBP, TG, HDL-C, and LDL-C, multivariate logistic regression analysis found no association between H. pylori infection and diabetes (OR 1.02, 95% CI 0.88-1.18). Additionally, subgroup analysis indicated that H. pylori infection was significantly associated with increased risk of diabetes in the female group (OR 1.09, 95% CI 1.08-1.09). Conclusions. No significant association was found between H. pylori infection and diabetes. However, the subgroup analysis suggested that H. pylori infection was possibly associated with increased risk of diabetes among females. Future cohort studies are needed to verify this association in females and to address possible implication in the prevention of diabetes.